(3GdQSGdI GdhGRYI dUGdM GdCeI Yf GdGYJQGV Ydi GdCFeIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CaGV YdjfG CfhGQkG ef eTcGI GdYQaGf hHYO , aEf Gddg deG Yde ai bjGe GdCFeI ef UdGM GdNdb hef CLd Pdc fGW HBQGFge CMcGe GdTQjYI , hLYdgG ehchdg Edi BQGFge s
(3BNQgG (B:s
(3bd gPg eSCdJi COYh Gddg Ydi HUjQI hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs